Dilute aPTT Prolongation by Antiphospholipid Antibodies in Patients with Liver Cirrhosis - Violi, Francesco; Ferro, Domenico; Quintarelli, Claudio; Alessandri, Cesare; Saliola, Mirella; Valesini, Guido; Balsano, Francesco (Thrombosis and Haemostasis, 1990)
The behaviour of aPTT, as assessed by standard or diluted phospholipid mixture, was investigated in 20 patients suffering from liver cirrhosis. Standard aPTT was prolonged in 13 but it was corrected by 1:1 mixture with normal plasma. Dilute aPTT performed in samples mixed 1:1 with normal plasma and calculated by the difference in time between 1:80 and 1:5 phospholipid mixture was prolonged in 9 patients, who had also significantly higher titre of anticardiolipin antibodies (p <0.005). Unlike patients’ plasma with normal dilute aPTT, the addition of 0.05 M PC/PS liposomes to patient’s plasma with prolonged dilute aPTT significantly shortened dilute aPTT (p <0.001).This study shows the presence of antiphospholipid antibodies in some patients with liver cirrhosis; this seems to be responsible for the prolongation of dilute aPTT.